Cirurgia ortognática : protocolos de sobreposição tridimensional de tomografias e um novo parâmetro virtual para definir a sequência cirúrgica - Andriola, Fernando de Oliveira (2022)
Orthognathic surgery is a routine procedure performed to treat dentofacial deformities, leading to optimal clinical, aesthetic, and functional results. The computed tomography images are essential for pre- and postoperative assessments, as well as for diagnosis, three-dimensional virtual planning and outcomes evaluation. Virtual surgical planning is currently considered state-ofthe-art towards achieving better results, and the superposition of computed tomography scans has become the gold standard for postoperative evaluation of changes and surgical results, as well as the precision of the surgical techniques. This thesis is divided into two parts: (1) the first is a systematic review that aims to identify, compare and synthesize the current scientific evidence about the three-dimensional superimposition methods of conventional and cone-beam computed tomography used to evaluate hard tissue changes after orthognathic surgery, considering accuracy, reproducibility and efficiency. It was performed following the PRISMA criteria, and the search was divided into Main Search (PubMed, EMBASE, Cochrane Library, LILACS, and SciELO), Grey Literature search (Google Scholar and Open Grey) and Manual search. The accuracy of most methods was high, showing mean differences smaller than voxels’ dimensions, ranging between 0.05 and 1.76 mm for translational accuracy, and 0.10– 1.09° for rotational accuracy. The overall reproducibility was considered good as demonstrated by the small mean error (range: 0.01–0.26 mm) and high correlation coefficients (range: 0.53–1.00). Time to complete superimposition protocols ranged between a few seconds up to 40 minutes. Voxel-based superimposition protocols presented the highest accuracy and reproducibility, and superimposition protocols that used automated processes and only one software were the most efficient. In the second part (2), a new virtual parameter is presented to help in decision making between operating the maxilla or the mandible first in bimaxillary orthognathic surgeries. By virtually evaluating the amount of mandibular autorotation necessary to create the intermediate surgical splint in each sequence, it was possible to assess the differences between them and to suggest which surgical movements and clinical characteristics can be better treated when each sequence is used. Three-dimensional virtual surgical plannings of 194 patients were included and, and subgroup analyses were carried out using one-way ANOVA. Maxilla-first is indicated for cases with Le Fort I posterior intrusion, skeletal class III, and cases with anterior open bite, while the mandible-first transfer is recommended for Le Fort I global extrusion, especially if correcting cant asymmetries.